2020
DOI: 10.1186/s42523-020-00027-7
|View full text |Cite
|
Sign up to set email alerts
|

Domesticated equine species and their derived hybrids differ in their fecal microbiota

Abstract: Background: Compared to horses and ponies, donkeys have increased degradation of dietary fiber. The longer total mean retention time of feed in the donkey gut has been proposed to be the basis of this, because of the increased time available for feed to be acted upon by enzymes and the gut microbiota. However, differences in terms of microbial concentrations and/or community composition in the hindgut may also underpin the increased degradation of fiber in donkeys. Therefore, a study was conducted to assess if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 74 publications
4
35
0
Order By: Relevance
“…Most of the bacterial taxa of this core lack cultured representation; their availability is essential to gain fundamental knowledge of the microbial functions that underpin the equine hindgut ecosystem and that of the donkey in particular. In another trial, Edwards et al [ 8 ] found that donkey fecal microbiota differed from that of both pony and pony × donkey, and these differences were related to a higher abundance and diversity of taxa with known (or speculated) roles in fiber degradation. The findings of these trials suggest that the specific composition of hindgut microbiota of donkeys plays an essential role in fiber digestion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the bacterial taxa of this core lack cultured representation; their availability is essential to gain fundamental knowledge of the microbial functions that underpin the equine hindgut ecosystem and that of the donkey in particular. In another trial, Edwards et al [ 8 ] found that donkey fecal microbiota differed from that of both pony and pony × donkey, and these differences were related to a higher abundance and diversity of taxa with known (or speculated) roles in fiber degradation. The findings of these trials suggest that the specific composition of hindgut microbiota of donkeys plays an essential role in fiber digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Their large intestine leads to a higher digestibility of organic matter, gross energy and fiber fractions than in horses or ponies [ 4 , 5 , 6 ]. According to Edwards et al [ 7 , 8 ], donkeys have a fecal microbiota concentration and a community composition that differ from those of other equine types, and this diversity plays an essential role in fiber digestion. Liu et al [ 9 ] studied the microbiota at different sites of the gastrointestinal tract of donkeys, finding a higher microbial concentration in the hindgut than in the foregut.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic fungi were reported to be present in domesticated and non-domesticated equine species, with the AF community composition in horses and ponies being more similar to zebras than donkeys (Edwards et al, 2020b). In a separate study, AF diversity in donkeys was shown to be higher when compared to that of ponies and pony × donkey hybrids (Edwards et al, 2020a). Several studies have revealed that the genus Khoyollomyces (formerly known as AL1) is almost exclusively found in equines (Liggenstoffer et al, 2010;Mura et al, 2019;Edwards et al, 2020b;Hanafy et al, 2020).…”
Section: Influence Of Host On Anaerobic Fungi Communitymentioning
confidence: 98%
“…Anaerobic fungi were reported to be present in domesticated and non-domesticated equine species, with the AF community composition in horses and ponies being more similar to zebras than donkeys (Edwards et al, 2020b). In a separate study, AF diversity in donkeys was shown to be higher when compared to that of ponies and pony × donkey hybrids (Edwards et al, 2020a). Several studies have revealed that the genus Khoyollomyces (formerly known as AL1) is almost exclusively found in equines Mura et al, 2019;Edwards et al, 2020b;Hanafy et al, 2020).…”
Section: Influence Of Host On Anaerobic Fungi Communitymentioning
confidence: 98%